A System Dynamics Model of Urban Rainstorm and Flood Resilience to Achieve the Sustainable Development Goals - Li, Wen; Jiang, Rengui; Wu, Hao; Xie, Jiancang; Zhao, Yong; Song, Yingxue; Li, Fawen (Sustainable cities and society, 2023)
•The urban flood resilience framework was established using SDGs as a guideline.•A system dynamics model used to develop urban flood resilience.•Sensitive factors affecting flood resilience in rainstorm scenarios were identified.•Six policy scenarios were set to find the drivers of flood resilience in urban systems.•The results showed that the growth of flood resilience experienced three phases by 2035. The combined effects of climate change and accelerated urbanization have increased the risk of urban rainstorm and flood disasters, which seriously affects the achievement of the Sustainable Development Goals (SDGs) in cities. Improving urban flood resilience is one of main ways to deal with flooding. This study established an urban rainstorm and flood resilience model to sort out the behavioral mechanisms of multiple subjects (government, flood control department, residents and media) and the internal action mechanisms from different dimensions (economic, social, natural, infrastructure and information) of urban rainstorm and flood resilience using system dynamics approach, and to investigate the urban rainstorm and flood resilience in Xi'an city. The results show that the damage losses rate reduced by 44.44%, 10.8%, 9.48% and 3.37% by improving flood resilience, resident engagement, government attention degree and information construction level, respectively. The degree of improvement of urban rainstorm and flood resilience varied for six development scenarios when predict flood resilience. The development pattern can be divided into the beginning phase, preparation phase and development phase, and three improvement strategies are proposed based on the development pattern of flood resilience. This study helps to provide refined strategies for urban rainstorm and flood resilience assessment construction.